Pedampingan Penggunaan Sistem Informasi Profil Desa Banyuasin Berbasis Internet Dan Aplikasi Mobile - Ghiri Basuki Putra; Eddy Jajang Jaya Atmaja (STMIK Royal, 2021)
Abstract: The development of information and communication technology is currently growing rapidly and has touched almost all levels of society. With the advancement of information technology, the dissemination of information is accelerating and is not limited to space and time. The village is currently getting special attention from the government with the large budget given to each village to advance rural villages in Indonesia. However, these funds are still very minimal for development in the field of information technology. In fact, every village needs information technology, especially information systems to help the performance of the village government in providing services to the community and to facilitate data and information management. This information system will provide complete information and facilitate the dissemination of information in the digital era by utilizing the Internet. Banyuasin Village does not yet have a village information system in managing data and information and for conveying information to the community. This service method is community education by conducting discussions, interviews, socialization and training for the system that has been built so that it can be used by the village of Banyuasin. The village information system that was built provided benefits in the field of information technology and made Banyuasin Village a mobile application-based Information and Communication Technology-based village. Keywords: information system; village profile; website Abstrak: Perkembangan teknologi informasi dan komunikasi saat ini semakin pesat dan telah menyentuh hampir ke seluruh lapisan masyarakat. Dengan kemajuan teknologi informasi menyebabkan penyebarluasan informasi semakin cepat dan tidak terbatas dengan ruang dan waktu. Desa saat ini mendapatkan perhatian khusus dari pemerintah dengan besarnya anggaran yang diberikan ke tiap desa untuk memajukan desa desa di Indonesia. Hanya saja, dana tersebut masih sangat minim untuk pengembangan di bidang teknologi Informasi. Padahal setiap desa membutuhkan teknologi informasi terutama sistem informasi untuk membantu kinerja pemerintah desa dalam memberikan layanan kepada masyarakat serta memudahkan dalam pengelolaan data dan informasi. Sistem informasi ini akan memberikan informasi lengkap dan dan memudahkan penyebarluasan informasi pada era digital dengan pemanfaatan Internet. Desa Banyuasin belum mempunyai sistem informasi desa dalam pengelolaan data dan informasi serta untuk menyampaikan informasi ke masyarakat. Metode pengabdian ini adalah pendidikan masyarakat dengan melakukan diskusi, wawancara, sosialisasi dan pelatihan untuk sistem yang telah dibangun agar dapat digunakan oleh desa Banyuasin. Sistem informasi desa yang di bangun memberikan manfaat di bidang teknologi informasi dan membuat Desa Banyuasin menjadi desa yang berbasis Teknologi Informasi dan Komunikasi berbasis aplikasi mobile. Kata kunci : profil desa; sistem informasi; website